1993
DOI: 10.1128/jb.175.21.6873-6880.1993
|View full text |Cite
|
Sign up to set email alerts
|

Genes encoding two isocitrate dehydrogenase isozymes of a psychrophilic bacterium, Vibrio sp. strain ABE-1

Abstract: The genes coding for two structurally different isocitrate dehydrogenase isozymes (IDH-I and IDH-II) of a psychrophilic bacterium, Vibrio sp. strain ABE-1, were cloned and sequenced. Open reading frames of the genes (iedI and iedII) are 1,248 and 2,229 bp in length, respectively. The amino acid sequences predicted from the open reading frames of iedI and icdII corresponded to the N-terminal amino acid sequences of the purified IDH-I and IDH-II, respectively. No homology was found between the deduced amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 35 publications
(26 reference statements)
2
77
0
Order By: Relevance
“…Thirdly, a further indication that cold-active promoters might be involved in adaptation to low temperature has been found in a psychrophilic Vibrio sp. : this organism expresses two structurally and genetically different isozymes of isocitrate dehydrogenase, and one of these, IDH-II, is extremely thermolabile and is encoded by a gene that contains a CCAAT motif in its promoter region (Ishii et al, 1993). In the present study, we found that pnp is cold inducible in Y. enterocolitica, and we showed that a 0.33 kbp region upstream of pnp is sufficient to retain its cold induction.…”
Section: Discussionsupporting
confidence: 56%
“…Thirdly, a further indication that cold-active promoters might be involved in adaptation to low temperature has been found in a psychrophilic Vibrio sp. : this organism expresses two structurally and genetically different isozymes of isocitrate dehydrogenase, and one of these, IDH-II, is extremely thermolabile and is encoded by a gene that contains a CCAAT motif in its promoter region (Ishii et al, 1993). In the present study, we found that pnp is cold inducible in Y. enterocolitica, and we showed that a 0.33 kbp region upstream of pnp is sufficient to retain its cold induction.…”
Section: Discussionsupporting
confidence: 56%
“…This sequence has 82z and 76z identity with those of C. maris IDH-II 22) and V. parahaemolyticus IDH, 2) respectively. The optimum temperature for activity of the puriˆed IDH was found to be 409 C, indicating that it is a typical mosophilic en- zyme.…”
Section: Resultsmentioning
confidence: 89%
“…Conversely, no such a similarity was found in the amino acid sequence deduced from the ORF2, nor was found homologs in the nucleotide and protein databases. In addition, alignment of the amino acid sequences of the bacterial monomeric type IDHs showed that ORF1 has a high amino acid sequence identity (66.2z and 62z) to the enzymes of C. maris 22) and Corynebacterium glutamicum, 6) respectively (Fig. 4).…”
Section: )mentioning
confidence: 99%
“…Two downstream primers were designed from the sequences of highly conserved regions of ICL genes cloned from various organisms (Rehman & McFadden, 1996) ; 5h-SCCATRTGNCCRCAYTTYTT-3h (20-mer) corresponding to KKCGHMA and 5h-CNARRTGN-CCRCAYTTYTT-3h (19-mer) corresponding to KKCGHLG. C. maris genomic DNA was isolated as described by Ishii et al (1993). Amplification was carried out for 30 cycles in a DNA thermal cycler 4800 (Perkin-Elmer) in 100 µl reaction mixture containing 1n3 µg genomic DNA, 200 pmol each forward and reverse primer and 2n5 U KOD DNA polymerase (Toyobo) in a buffer system prepared by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%